Effects of cutting parameters on aluminium alloys-A review. (2021) - Srivastava, Vishal Shankar; Gupta, Tarun Kumar; Srivastava, Ashish Kumar; Chauhan, Sandeep; Chauhan, Pankaj Kumar
Abstract: The current work is focused on the optimization of the machining process parameters and its effect on surface roughness and material removal rate for aluminium alloys. Aluminium alloy is a ductile material, during machining of aluminium alloy we select sincerely cutting speed, feed rate and depth of cut for better outcomes. Further to achieve optimum productivity at less cost different optimization use technique like as TAGUCHI, ANOVA, GRA, and RSM etc. This work highlight consequential parameters like cutting velocity of material, cutting depth and feeding rate that affect significantly the performance of CNC machining. TAGUCHI and ANOVA are mostly used software for optimization method and for better surface roughness i.e. Ra and Rz. The most influencing identified factors for material removal rate and surface roughness are feed rate whose value lies between 0.05 and 0.15 mm/min followed by depth of cut which is less than 1 mm. in most of the cases.